COVID-19 trepidation: repercussions on air travel anxiety, anger and trust among travellers. Issue 3 (2nd September 2022) - Tiwari, Mansi; Sharma, Deependra; Narula, Sumit
ABSTRACT: This paper aims to investigate how the fear of COVID-19 has impacted the air travel anxiety, anger and trust among the travellers of Ahmedabad and Gandhinagar, Gujarat by collecting the primary data and analyzing through a variance-based SEM approach. The data was collected from 150 travellers through the snowball sampling technique including people who travelled during unlocking of flights and experienced mental constraints before and during travelling. The study revealed that there is a positive and significant relationship between air travel anxiety and anger with fear of COVID-19 and a negative and significant relationship with trust. The current study has important implications for scholars as well as for airline management to understand how hard people are affected while travelling in the fear of COVID-19 and its spread. It would also help the administration to improve the conditions to ensure the safety of travellers. The paper concludes with a few sets of recommendations because people in India are horrified by the entry of the third variant of COVID-19.